PENGUATAN USAHA MIKRO KECIL MELALUI PELATIHAN DAN PENDAMPINGAN AKUNTANSI PERPAJAKAN DAN AKSES PERMODALAN - Umaimah, Umaimah; Suwarno, Suwarno (Jurnal Pengabdian Masyarakat dan Lingkungan, 2023)
The purpose of this activity is to strengthen Small Micro Enterprises (SME) in Dukuhkembar Village, Gresik Regency. Strengthening is carried out through training and mentoring so that the performance of the assisted SMEs is getting better and contributing to income, family welfare and all villagers. The initial data obtained regarding the problems of business actors in the village are; First, business actors still do not understand business financial records, there is no separation between business and personal finances. As a result, the determination of production costs, selling prices and profit calculations cannot be carried out; secondly understanding of tax obligations such as tax reporting for micro and small business actors is very minimal; the third is limited access to capital for business development. The solution in efforts to strengthen businesses is by: (1) conducting accounting training for micro and small businesses, (2) Training on financial administration & tax administration (3) Training on access to capital. After the training, monitoring, evaluation and assistance will be continued. The results obtained from this service program are strengthening businesses in 14 micro-small businesses in Dukuhkembar Village with skills in financial management, taxation, and access to capital so that businesses can grow and develop.